PENGARUH MODEL PEMBELAJARAN LIGHTENING LEARNING CLIMATE TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS X SMA NURUL FALAH - munengsih hanraein; Lely Lailatus Syarifah; Siti Nurliana; Puji Astutik Ningsih (Jurnal Muara Pendidikan, 2019)
The study aims at examining the effect of lightening the learning climate models on mathematics learning motivation in class X SMA Nurul Falah Kutabumi. This research method was used is quasi experiment with research design of “Nonequivalen Control Group”. The population in this research were student of class X IPA1 and X IPA2 SMA Nurul Falah Kutabumi with 39 students of class X IPA1 and 30 students in class X IPA2. Class X IPA1 is an experiment experiment class treated with the lightening the learning climate, while class X IPA2 is a control class with a conventional learning model. Data collection techniques use student motivation scale by observation (questioner), in depth interviews, and documentation. Data analysis techniques used quantitative descriptive statistics by comparing the average score of the posttest pretest to the learning motivation scale of the experiment class and the control class. The result showed that there was an effect of the lightening the learning climate models on students motivation to learn mathematics in class X. this can be seen from the calculation of the average score of the motivation scale. The average score of the pretest motivation scale of the experiment group was 72,55, while the control group was 72,03. The average posttest of the experiment group learning motivation scale was 80,89, while the control group was 75,58. From thes data, the average posttest score of the experiment class is greater than the control class. Besides the result of categorizing the average posttest of the experiment class learning motivation scale is better than the control class.